Wernicke's encephalopathy-induced hearing loss complicating sleeve gastrectomy. Issue 9 (15th September 2020) - Mohammed, Elaf Abdulnabi; Hajji, Sulaiman Ali; Aljenaee, Khaled; Ghanbar, Mohammad Ibrahim
Abstract : A 25-year-old woman brought to the hospital with symptoms of acute confusion, disorientation, diplopia, hearing loss and unsteady gait which started 4 days prior to her presentation with rapid worsening in its course until the day of admission. She had a surgical history of laparoscopic sleeve gastrectomy 2 months earlier which was complicated by persistent vomiting around one to three times per day. She lost 30 kg of her weight over 2 months and was not compliant to vitamin supplementation. CT of the brain was unremarkable. Brain MRI was done which showed high signal intensity lesions involving the bilateral thalamic regions symmetrically with restricted diffusion on fluid-attenuated inversion recovery imaging. Other radiological investigations, such as magnetic resonance venography and magnetic resonance angiography of the brain were unremarkable. An official audiogram confirmed the sensorineural hearing loss. A diagnosis of Wernicke's encephalopathy due to thiamin deficiency post-sleeve gastrectomy was made based on the constellation of her medical background, clinical presentation and further supported by the distinct MRI findings. Consequently, serum thiamin level was requested and intravenous thiamin 500 mg three times per day for six doses was started empirically, then thiamin 250 mg intravenously once daily given for 5 more days. Marked improvement in cognition, eye movements, strength and ambulation were noticed soon after therapy. She was maintained on a high caloric diet with calcium, magnesium oxide, vitamin D supplements and oral thiamin with successful recovery of the majority of her neurological function with normal cognition, strength, reflexes, ocular movements, but had minimal resolution of her hearing deficit. Serum thiamin level later was 36 nmol/L (67–200).